Coronavirus replication and pathogenesis: Implications for the recent outbreak of severe acute respiratory syndrome (SARS), and the challenge for vaccine development - Navas-Martín, Sonia (J Neurovirol, 2004)
A novel coronavirus has been recently identified as the causative agent of the severe acute respiratory syndrome (SARS) outbreak that has accounted for more than 8000 infected people worldwide. This review will discuss current knowledge on coronavirus replication, pathogenesis, evolution, and vaccine strategies, as well as the most recent findings on SARS coronavirus.